2015
DOI: 10.1038/srep13366
|View full text |Cite
|
Sign up to set email alerts
|

Study of spin-ordering and spin-reorientation transitions in hexagonal manganites through Raman spectroscopy

Abstract: Spin-wave (magnon) scattering, when clearly observed by Raman spectroscopy, can be simple and powerful for studying magnetic phase transitions. In this paper, we present how to observe magnon scattering clearly by Raman spectroscopy, then apply the Raman method to study spin-ordering and spin-reorientation transitions of hexagonal manganite single crystal and thin films and compare directly with the results of magnetization measurements. Our results show that by choosing strong resonance condition and appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…11 This technique makes it possible to record even minor crystal structure variations and to reveal the character of ion bonds, which can arise from magnetic ordering and magnetoelectric polarization. 12,13 The features of the huntite vibrational spectrum caused by the magnetic phase transitions have been studied. Adem et al 14 studied Raman spectra of the TbFe 3 (BO 3 ) 4 crystal.…”
Section: Introductionmentioning
confidence: 99%
“…11 This technique makes it possible to record even minor crystal structure variations and to reveal the character of ion bonds, which can arise from magnetic ordering and magnetoelectric polarization. 12,13 The features of the huntite vibrational spectrum caused by the magnetic phase transitions have been studied. Adem et al 14 studied Raman spectra of the TbFe 3 (BO 3 ) 4 crystal.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the anomalously broad linewidth of spin wave in a single magnetic material, our recent studies showed anomalous behaviors of spin wave linewidth and lineshape between LuMnO 3 single crystal and HoMnO 3 thin film [87,89]. The spin wave linewith is much broader and the lineshape is much more asymmetric in single crystal comparing with that in thin film.…”
Section: Broad Linewidthmentioning
confidence: 90%
“…In recent years, magnetic excitations in magnetoelectric multiferroics have been attracted much research interests [76][77][78][79][80][81][82][83][84][85][86][87][88][89]. The magnetic excitations in multiferroic hexagonal manganites have been systematically investigated through resonance and polarization Raman scattering experiments [81,82,87,89]. The resonance Raman scattering study indicated that the spin wave scattering in hexagonal manganites can be selectively excited with red lasers, which is correlated with the resonance condition of on-site Mn d-d transition (more details of resonance selection is discussed in section 4) [82].…”
Section: Anti-stokes To Stokes Intensity Ratiomentioning
confidence: 99%
“…Raman selection rule can help establish the excitations of the magnetic origin with high resolution 22 , 23 . Previous Raman studies show that the spin excitations strongly correlated with a particular electronic transition are observed in hexagonal R MnO 3 below the T N 24 – 28 . Spin excitations of relatively high energy (~ 0.1 eV) are optically excited in the hexagonal R MnO 3 system through the resonance with the Mn d – d transition 24 , 28 – 30 .…”
Section: Introductionmentioning
confidence: 93%